2011
DOI: 10.1590/s0004-282x2011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Headache is associated with lower alcohol consumption among medical students

Abstract: The aim of this study was to investigate the association between headache and alcohol consumption among medical students. 480 medical students were submitted to a questionnaire about headaches and drinking alcohol. Headache was assessed by IDMigraine and functional disability was evaluated with MIDAS. The evaluation of alcohol consumption was assessed with Alcohol Use Disorders Identification Test (AUDIT). There was significantly lower proportion of students with drinking problem among students with headache. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…A Brazilian cross‐sectional, community‐based study among medical students indicates that this assumption is valid . This report investigated the association between headache and alcohol consumption among medical students and found that students with headache, both migraine and non‐migrainous headache, used less alcohol and had less alcohol‐related disorders.…”
Section: Review Of Studies With Discussion Of Important Questions Andmentioning
confidence: 96%
“…A Brazilian cross‐sectional, community‐based study among medical students indicates that this assumption is valid . This report investigated the association between headache and alcohol consumption among medical students and found that students with headache, both migraine and non‐migrainous headache, used less alcohol and had less alcohol‐related disorders.…”
Section: Review Of Studies With Discussion Of Important Questions Andmentioning
confidence: 96%
“…(1) Among migraine patients who did not drink alcohol at all (about 50%), only 3% reported that abstaining from alcohol was a result of alcohol as a migraine trigger; [27] (2) differently with we can expect if ADs trigger migraine, an higher use of ADs was reported in chronic migraine in comparison whit episodic migraine; [64] (3) the percentage of subjects who never or seldom consume ADs is higher in migraine and nonmigraine headache, [63,65,66] which suggests that factors other than previous experience of alcohol as a trigger can contribute to reduced alcohol consumption in migraine, such as personal preference. [4] The possible triggering site However, if ADs are a trigger factor of virtually all primary headaches, a fundamental question emerges: That is if ADs act at different levels in triggering the primary headaches or do they act at an initial level of a common pathogenetic pathway.…”
Section: Th % M %mentioning
confidence: 99%
“…From those studies, red wine in particular was suggested as a trigger factor, with rapid onset of headache after consumption [14,16,17]. It has been hypothesized that susceptibility to alcohol might affect behavior, leading to less alcohol consumption or abstention by patients with migraine [18][19][20][21][22], but the reasons for patients with migraine to abstain from alcohol consumption have not been explored in detail.…”
Section: Introductionmentioning
confidence: 99%